PENGARUH CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN(STUDI PADA PERUSAHAAN MANUFAKTUR SUB INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023) - Ariyanto Adi Santoso; Surenggono Surenggono (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study examines the influence of Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), and Intellectual Capital (IC) on the financial performance of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2021-2023. Using a quantitative approach, this study employed purposive sampling to determine the research sample, resulting in a total of 22 companies. Multiple linear regression analysis was applied as the analytical technique to analyze financial performance through Return on Assets (ROA). The results show that CSR, GCG, and IC simultaneously and significantly affect ROA. However, partially, CSR and GCG do not significantly affect ROA, while IC significantly affects ROA. This research provides empirical evidence on the importance of IC compared to CSR and GCG in boosting financial performance in food and beverage companies. It also provides insights for managers on how to prioritize IC while maintaining GCG and CSR practices to support sustainable company growth.